STUDYING STUDENT STATISTICAL LITERACY IN STATISTICS LECTURES ON HIGHER EDUCATION USING GROUNDED THEORY APPROACH - Lukman Lukman; Wahyudin Wahyudin; Didi Suryadi; Dadan Dasari; Sufyani Prabawanto (Jurnal Infinity, 2022)
The purpose of this study was to obtain an overview of the student's Statistical Literacy model in Statistics learning in Higher Education. Researchers conducted an in-depth study of student statistical literacy, how they understand and apply statistics, how statistics are used as a tool for reliable data that can be trusted as scientific works. The research method uses qualitative research methods with a Grounded Theory approach. Participants involved in this study were 114 participants from several universities in West Java, Indonesia. The results of this study found a student statistical literacy model consisting of 2 dimensions and 5 elements. Dimensions of Statistical Knowledge: Descriptive Statistics, Inference Statistics, Statistical Communication and Statistical Reasoning. Attitude Dimensions: Confidence and Critical Attitude.